VD_FINDINFO Jug / 2022 / 460 vom 22. April 2022 - VD Tribunal cantonal (2022)
VIOLATION DES RÈGLES DE LA CIRCULATION, ENTRAVE AUX SERVICES D'INTÉRÊT GÉNÉRAL | 106 CP, 239 CP, 286 CP, 48 let. a ch. 1 CP, 49 al. 1 CP, 26 al. 1 LCR, 90 al. 1 LCR